Divergence in Coding Sequence and Expression of Different Functional Categories of Immune Genes between Two Wild Rodent Species. (10th February 2021) - Zhong, Xiuqin; Lundberg, Max; Råberg, Lars
Abstract: Differences in immune function between species could be a result of interspecific divergence in coding sequence and/or expression of immune genes. Here, we investigate how the degree of divergence in coding sequence and expression differs between functional categories of immune genes, and if differences between categories occur independently of other factors (expression level, pleiotropy). To this end, we compared spleen transcriptomes of wild-caught yellow-necked mice and bank voles. Immune genes expressed in the spleen were divided into four categories depending on the function of the encoded protein: pattern recognition receptors (PRR); signal transduction proteins; transcription factors; and cyto- and chemokines and their receptors. Genes encoding PRR and cyto-/chemokines had higher sequence divergence than genes encoding signal transduction proteins and transcription factors, even when controlling for potentially confounding factors. Genes encoding PRR also had higher expression divergence than genes encoding signal transduction proteins and transcription factors. There was a positive correlation between expression divergence and coding sequence divergence, in particular for PRR genes. We propose that this is a result of that divergence in PRR coding sequence leads to divergence in PRR expression through positive feedback of PRR ligand binding on PRR expression. When controlling for sequence divergence, expression divergence of PRR genes did not differ from other categories. Taken together, the results indicate that coding sequence divergence of PRR genes is a major cause of differences in immune function between species.